Penerapan Quality Control pada Souvenir Logo PNP dengan Metode Box Plot dan Six Sigma - Menhendry Menhendry; Alfian Alfian; Elvis Adril; Junaidi Junaidi; Zulhendri Zulhendri (Politeknik Negeri Padang, 2021)
The quality of a product determines the level of market demand. This paper discusses the determination of the quality level of plastic molding with the sigma level method which uses the Box Plot to determine the desired quality limit. The purpose of this research is to determine the level of quality of product using statistics. The object of this research is to determine the weight variation of the souvenir of PNP logo with a weight indicator. The experiment were carried out on 200 samples taken at random.Then each sample is numbered from 1 to 200. Each sample is weighed carefully. The results obtained were processed using a box plot to obtain the numbered of rejected samples from 200 samples that were weighed. The result of data processing obtained 19 reject products from 200 products tested. From this data there are 9,5% of products that do not meet the desired specifications. Furthermore, the sigma level is determined from the results of data processing using a box plot. DPMO of 9.5% is 95000 Defects per Milion Opportunities. The result of determining the sigma level is 2.8 Sigma.